T2 mapping and readout segmentation of long variable echo-train diffusion-weighted imaging for the differentiation of parotid gland tumors. Issue 151 (June 2022) - Baohong, Wen; Jing, Zhu; Zanxia, Zhang; kun, Fu; Liang, Liu; Eryuan, Gao; Yong, Zhang; Fei, Han; Jingliang, Cheng; Jinxia, Zhu
Highlights: The purpose of this study was to investigate the differential diagnostic value of radial turbo spin-echo (TSE) T2 mapping and readout-segmented echo-planar imaging diffusion weighted image (RESOLVE DWI) in parotid gland tumors. T2 mapping, RESOLVE DWI, and the combination of the two methods can all be used to quantitatively diagnose differential parotid gland tumors. The combined effect of the two methods was similar to the effect when used alone. T2 value is comparable to ADC value. Abstract: Objective: To investigate the diagnostic value of radial turbo-spin-echo (TSE) T2 mapping and readout segmentation of long variable echo-train diffusion-weighted imaging (RESOLVE DWI) for the differentiation of parotid gland tumors. Materials and methods: One hundred and fifty-four patients with histopathologically confirmed parotid gland tumors were retrospectively recruited from June 2018 to May 2021 at the First Affiliated Hospital of Zhengzhou University. There were 111 benign tumors and 43 malignant tumors. Benign tumors were further divided into pleomorphic adenomas (n = 69) and Warthin's tumors (n = 26). All patients were scanned using T2 mapping and RESOLVE DWI. T2 and ADC values and a combination of the two methods were compared and analyzed for the ability to differentiate parotid gland tumor types. Results: The T2 and ADC values of benign tumors were significantly higher than those of the malignant tumors (127.97 ± 56.29 ms vs 97.53 ± 45.24 ms, 1.27 ± 0.40 × 10 −3 mm 2 /s vs 1.00 ± 0.39 × 10 −3 mm 2 /s, all P < 0.05). The area under the curve (AUC) of the T2 and ADC values for differentiating (1) benign and malignant parotid tumors, (2) pleomorphic adenomas and Warthin's tumors, (3) pleomorphic adenomas and malignant tumors, and (4) Warthin's tumors and malignant tumors were 0.709 and 0.715, 0.918 and 0.994, 0.748 and 0.774, and 0.665 and 0.659, respectively, with no significant differences observed between the T2 and ADC values (all P > 0.05). There were no significant differences in these values among the three tumor groups (malignant tumor, pleomorphic adenoma, and Warthin's tumor groups, all P > 0.05). Conclusions: T2 mapping and RESOLVE DWI can be used to differentiate various parotid gland tumors. T2 values are comparable to ADC values.